1979
DOI: 10.1159/000122875
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of K<sup>+</sup> and Ca<sup>++</sup> on <i>α</i>-MSH and ACTH Release from Superfused Neurointermediate Lobe of the Rat Hypophysis

Abstract: The effects of K+-enhanced and Ca++-free media on α-MSH and adrenocorticotropic hormone (ACTH) release from superfused neurointermediate lobe (NIL) were studied in the same experiments. High K+ caused reversible and repeatable inhibition of α-MSH release and stimulation of ACTH release. Removal of Ca++ impaired the effect of K+, irreversibly for α-MSH and reversibly for ACTH. The existence of both melanotrophic and corticotrophic cells within the intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
(14 reference statements)
3
10
0
Order By: Relevance
“…Indeed, instead of sti mulating hormonal release as a result of depolarizing of the cellular membrane, high K+, on the contrary, appears to in hibit release of a-MSH and (3-endorphin [23,33,36). Tilders et al [33] have demonstrated that in the rat, this effect is caused by DA release from nerve endings at the levels of the IL which, in turn, inhibits a-MSH secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, instead of sti mulating hormonal release as a result of depolarizing of the cellular membrane, high K+, on the contrary, appears to in hibit release of a-MSH and (3-endorphin [23,33,36). Tilders et al [33] have demonstrated that in the rat, this effect is caused by DA release from nerve endings at the levels of the IL which, in turn, inhibits a-MSH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Two perifusion chambers, containing 40-50 NIL (from I-day-old mice), 25-30 NIL (from 7-day-old mice), or 10 NIL (from adults), were perifused with the aid of a constant flow (2 m l/ 10 min) of Krebs-Ringer (KR) bicarbonate buffer as we have previ ously described [23]. When the K* concentration was enhanced from 5.95 to 47.5 pM (8 K*), the concentration of NaCI was adjust ed to maintain iso-osmotic conditions.…”
Section: Superfusion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has recently been shown that 45 mM-K stimulates the co-ordinated release of several melanotroph products, including melanocyte-stimulating hormone (Jackson et al 1981). Earlier studies on hormone release had shown no stimulatory effect ofexcess K, possibly because the preparations used contained inhibitory nerve endings (Schmitt, Briaud, Mialhe & Stutinsky, 1979;Tilders, van der Weude, Swaab & Mulder, 1979). In addition, if hormone release depends on the activation ofpotential-dependentCa channels which rapidly inactivate, the duration of the response will be limited; such may have been the explanation for the failure of Bower & Hadley (1972) to detect stimulation of mouse melanotrophs.…”
Section: Stimulation Of [3h]methyltriphenylphosphonium Ion Efflux By mentioning
confidence: 99%
“…Tilders [30] and Tilders et al [33] reported a time dependency of the ratio of Received: November 3,1982 Accepted after revision: March 14, 1983 aMSH immunoactivity to ACTH bioactivity released from perifused neurointermediate lobes (NI) and differential stimulation by /-isoproterenol of species of ACTH bioactiv ity and ACTH, aMSH and |3END immunoactivity. Fur thermore, elevated K* concentration inhibits the release of aMSH but stimulates the release of ACTH bioactivity [21,23,26, 30]. Mains and Eipper [ 16] showed that /-isoproteren ol causes the release from pituitary tumor cells of aMSH, yLPH and N-terminal immunoactive peptides that are not released under basal conditions.…”
mentioning
confidence: 99%